فاعلية نموذج تسريع التعلم في تدريس العلوم على الاتجاه نحو المادة لدى طالبات الصف الأول المتوسط - الزهراني، سعاد راشد; الغامدي، فوزية خميس سعيد (جامعة المنصورة - كلية التربية, 2020)
هدفت الدراسة إلى التعرف على فاعلية نموذج تسريع التعلم على التحصيل الدراسي والاتجاه نحو ماده العلوم لدى طالبات الصف الأول المتوسط، ولتحقيق أهداف الدراسة تم استخدام المنهج التجريبي وفق التصميم الشبه التجريبي للمجموعتين التجريبية والضابطة، وتكونت عينة الدراسة من (88) طالبة من طالبات الصف الأول المتوسط بمنطقة الباحة، تم اختيارهن بطريقة عشوائية، وزعن على مجموعتين، مجموعة تجريبية عددها (44) طالبة تم تدريسها الوحدة الخامسة (تباين الحياة) من مادة العلوم وفق نموذج تسريع التعلم، ومجموعة ضابطة عددها (44) طالبة درست بالطريقة الاعتيادية. وتمثلت أدوات الدراسة في اختبار تحصيلي، ومقياس الاتجاه نحو العلوم من إعداد الباحثة، وتم التحقق من دلالات صدق وثبات المقياس قبل تطبيقه. وكشفت نتائج الدراسة عن وجود فروق دالة إحصائيا بين متوسطات درجات طالبات المجموعة التجريبية في القياسين القبلي والبعدي للاختبار التحصيلي بمستوياته (التذكر، الفهم، التطبيق، الدرجة الكلية للاختبار)، لصالح التطبيق البعدي، كما تبين وجود فروق دالة إحصائيا بين متوسطات درجات طالبات المجموعتين التجريبية والضابطة في التطبيق البعدي للاختبار التحصيلي بمستوياته، لصالح مجموعة الدراسة التجريبية، وبلغت نسبة الكسب المعدل لبلاك في المجموعة التجريبية ضمن القياسين القبلي والبعدي للاختبار التحصيلي (1.33). ووجدت فروق دالة إحصائيا بين متوسطات درجات طالبات المجموعة التجريبية في القياسين القبلي والبعدي لمقياس الاتجاه نحو مادة العلوم بأبعاده (الاتجاه نحو طبيعة العلوم، والاتجاه نحو الاهتمام بمادة العلوم، والاتجاه نحو قيمة العلوم، والاتجاه نحو معلمة العلوم، والدرجة الكلية للمقياس، لصالح التطبيق البعدي، كما تبين وجود فروق دالة إحصائيا بين متوسطات درجات طالبات المجموعتين التجريبية والضابطة في التطبيق البعدي لمقياس الاتجاه نحو مادة العلوم بأبعاده والدرجة الكلية، لصالح المجموعة التجريبية، وبلغت نسبة الكسب المعدل لبلاك في المجموعة التجريبية ضمن القياسين القبلي والبعدي لمقياس الاتجاه نحو مادة العلوم (1.22). كذلك كشفت نتائج الدراسة عن وجود علاقة ارتباطية دالة بين التحصيل في العلوم والاتجاه نحو المادة. وبناء على النتائج السابقة أوصت الدراسة بتبني النموذج في تدريس العلوم، بدلا من التركيز على طرق التدريس الاعتيادية، وتوجيه المشرفات التربويات إلى أهمية متابعة وتشجيع معلمات العلوم على عدم الاقتصار على الأساليب المعتادة في التدريس؛ حيث أظهرت نتائج الدراسة فاعليته في التحصيل والاتجاه نحو المادة.
The objective of the study was to identify the effectiveness of the accelerated learning model on the academic achievement and the attitudes towards science among female students in the first middle grade. In order to achieve the objectives of the study, the experimental method was used according to the semi-experimental design for the experimental and control groups. The study sample consisted of (88) female students of the first middle grade in the Al Baha region whom were randomly selected. The students were distributed on two groups. The first group is the experimental group, which consist of (44) students who were taught the fifth unit (life variance) of the science curriculum according to the accelerated learning model. The second group is the control group, which consist of 44 students, who were taught by the traditional method. The study tools were the achievement test and the scale of the trend towards science that was prepared by the researcher. The validity and stability of the scale were verified before it was applied. The findings revealed the existence of statistically significant differences between the mean scores of the experimental group students in the pre and post achievement test on each of its levels (recalling, comprehension, application, total score of the test) in favor of the post-application. There were statistically significant differences between the means scores of the experimental group students in the post achievement test on each of its levels in favor of the experimental group. The modified Blake's gain ratio in the experimental group in the pre and post achievement test was (1.33). The findings revealed the existence of statistically significant differences between the mean scores of the experimental group students in the pre and posttests of the scale of the trend towards science on all of its dimensions and total score of the scale for the post application. There were statistically significant differences between the mean scores of students of the experimental and control groups in the post-application on the scale of the trend towards the science curriculum at all of its dimensions in favor of the experimental group. The modified Blake's gain ratio in the experimental group on the pre and posttests of the scale of the trend towards the science curriculum (1.22). Moreover, the findings of the study revealed that there is a correlation between the achievement in science and the trend towards science. Based on the aforementioned findings, the researcher recommended adopting the accelerated learning model in teaching science, rather than focusing on the traditional teaching methods. Furthermore, the researcher suggested guiding educational supervisors towards the significance of follow up and motivating science teachers not to be limited to the traditional teaching methods as the findings indicated its effectiveness in science academic achievement and the trend towards science.
Keywords: التعليم المتوسط -- تدريس العلوم -- التحصيل الدراسي -- اتجاهات الطلبة -- الاتجاه نحو العلوم -- النماذج التدريسية -- نموذج تسريع التعلم